Novel mitochondrial electron transport-chain inhibitors as potencial antimalarial agents - Rodrigues, Tiago Correia de Oliveira, 1982- (2011)
Tese de doutoramento, Farmácia (Química Farmacêutica e Terapêutica), Universidade de Lisboa, Faculdade de Farmácia, 2010